A fault injection analysis of Virtex FPGA TMR design methodology - Lima, F.; Carmichael, C.; Fabula, J.; Padovani, R.; Reis, R. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2002)
This paper presents the meaningful results of a single bit upset fault injection analysis performed in Virtex FPGA triple modular redundancy (TMR) design. Each programmable bit upset able to cause an error in the TMR design has been investigated. Final conclusion using the TMR "golden" comparison method shows that "no errors" were reported by Virtex TMR design implementation in the presence of single bit upsets in the customization logic. The proton radiation ground test has confirmed the results achieved by fault injection.